2001
DOI: 10.3141/1747-05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variable Pricing on Temporal Distribution of Travel Demand

Abstract: Despite the potential of congestion pricing to ease the nation’s ever-increasing congestion problems, there is little quantitative evidence of its ability to spread peak travel demand more efficiently over the course of the day. The objective of the present work is to assess the impact of variable pricing on the temporal distribution of demand to investigate further the role of variable pricing as a travel demand management tool. The Variable Pricing Program of Lee County, Florida, was used as the data source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…The direct elasticities of the different demand segments with respect to tolls were calculated (see Table 7). In all cases, the demand was inelastic with an average elasticity of -0.143, which is consistent with previous research (Oum et al 1990;Cain et al 2001;Burris and Pendyala 2002). As a technical comment, it is important to note that, since cross-effects between the tolls at different time periods were not taken into account when computing the elasticities, it is likely that the elasticities overestimate the impact of pricing because they did not take into account how the lower toll rate in the off-peak periods, for instance, impacts the demand during the peak hours.…”
Section: Fig 3 Difference Between Stated and Actual Tolls-new Jerseysupporting
confidence: 90%
“…The direct elasticities of the different demand segments with respect to tolls were calculated (see Table 7). In all cases, the demand was inelastic with an average elasticity of -0.143, which is consistent with previous research (Oum et al 1990;Cain et al 2001;Burris and Pendyala 2002). As a technical comment, it is important to note that, since cross-effects between the tolls at different time periods were not taken into account when computing the elasticities, it is likely that the elasticities overestimate the impact of pricing because they did not take into account how the lower toll rate in the off-peak periods, for instance, impacts the demand during the peak hours.…”
Section: Fig 3 Difference Between Stated and Actual Tolls-new Jerseysupporting
confidence: 90%
“…The fixed-schedule congestion toll pricing is pre-determined, typically according to the historical traffic conditions by the time-of-day, usually seeking to shift the timing of travel demand from peak to off-peak periods [53,55,203,230,280]. Most of the current research focuses on the state-or congestion-dependent MCP, where optimal reactive congestion charges vary with the prevailing traffic conditions.…”
Section: The Within-day Dynamic Congestion Pricingmentioning
confidence: 99%
“…It has been shown that human trajectories have a high degree of temporal and spatial regularity and their mobility follows simple reproducible patterns [17]. The temporal distribution of human mobility also shows high unevenness [16]. Hence, the contacts between a sensor node and mobile nodes tend to arrive unevenly in temporal and Rush Hours, during which contacts arrive more frequently, exist widely in the environment.…”
Section: Motivationmentioning
confidence: 99%